Breeding for multi‐stress resilience in crops: Myth or possibility? - Khazaei, Hamid; Dodd, Ian C.; Ortiz, Rodomiro (John Wiley & Sons, 2026)
Climate change is increasing the frequency and intensity of combined abiotic and biotic stressors that may occur simultaneously or sequentially, dramatically reducing crop growth and yield stability. Plant breeding activities primarily target crop improvement for a single stressor, limiting crop resilience under complex environmental conditions. This opinion paper highlights the complexity of crop breeding for multi-stress growing conditions and discusses major challenges and opportunities to enable plant breeders to develop more climate-resilient crops. It also outlines the importance of integrating conventional breeding approaches with multi-omics and novel breeding technologies to develop multi-stress resilient crop cultivars. Identifying and validating key regulatory genes involved in multi-stress resilience and evaluating their performance across diverse genetic backgrounds, environments, and stress combination scenarios are needed. Although achieving complete multi-stress resilience remains an immense challenge, advances in integrative approaches and cross-disciplinary collaboration are steadily improving the potential to enhance crop resilience to multiple environmental stresses.
Keywords: abiotic and biotic stresses; climate-smart crops; environmental stresses interactions; foodsecurity; plant breeding